2012
DOI: 10.1038/ismej.2012.48
|View full text |Cite
|
Sign up to set email alerts
|

Influence of geogenic factors on microbial communities in metallogenic Australian soils

Abstract: Links between microbial community assemblages and geogenic factors were assessed in 187 soil samples collected from four metal-rich provinces across Australia. Field-fresh soils and soils incubated with soluble Au(III) complexes were analysed using three-domain multiplex-terminal restriction fragment length polymorphism, and phylogenetic (PhyloChip) and functional (GeoChip) microarrays. Geogenic factors of soils were determined using lithological-, geomorphological-and soil-mapping combined with analyses of 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 40 publications
4
52
0
Order By: Relevance
“…Geogenic factors were determined using geologic-, regolith-and soil-mapping criteria combined with geochemical analyses for 49 elements, pH and electrical conductivity in the soil samples. Multivariate statistical analyses showed the concentration of elements in soils was strongly linked to the underlying gold deposit and regolith landform ( Figure 9C); note the example shown in Figure 9C,D relates to one of four case studies presented in Reith et al [54], i.e., the study of 62 samples collected at the Old Pirate deposit in Northern Territory of Australia. Here, canonical correlation coefficients were high (δ1 0.91; δ2 0.70), and CA1 and CA2 accounted for 34.2% and 12.0% of variation in the bacterial dataset, respectively ( Figure 9D).…”
Section: Bioindicatorsmentioning
confidence: 94%
See 2 more Smart Citations
“…Geogenic factors were determined using geologic-, regolith-and soil-mapping criteria combined with geochemical analyses for 49 elements, pH and electrical conductivity in the soil samples. Multivariate statistical analyses showed the concentration of elements in soils was strongly linked to the underlying gold deposit and regolith landform ( Figure 9C); note the example shown in Figure 9C,D relates to one of four case studies presented in Reith et al [54], i.e., the study of 62 samples collected at the Old Pirate deposit in Northern Territory of Australia. Here, canonical correlation coefficients were high (δ1 0.91; δ2 0.70), and CA1 and CA2 accounted for 34.2% and 12.0% of variation in the bacterial dataset, respectively ( Figure 9D).…”
Section: Bioindicatorsmentioning
confidence: 94%
“…While the average concentrations of copper in soils are 25 μg g −1 , average gold concentrations lie in the range of a few ng g −1 [53]. For example, at Australian sites from which gold grains for DNA-fingerprinting of associated biofilms were obtained, ratios of copper to gold in soils lay between 25 and 9000 [54]. In areas where biogeochemical cycling of gold and copper has led to the formation of soil anomalies gold concentrations of up to 2 μg g −1 of gold were detected, whereas these soils can contain several hundred μg of copper g −1 of soil [55].…”
Section: Cupriavidus Metallidurans Ch34-putative Co-utilization Of Otmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, highly mobile elements, e.g., S, Zn, Cl, and Al, were implicated as drivers of bacterial community structures across these sites (21,22). A study of 187 soils collected at four naturally auriferous (i.e., Au-containing) areas in remote Australia has shown that microbial communities and functional potentials differ significantly with landform, soil depth, lithology, and Au deposits (23). This demonstrated that geogenic factors are important drivers of microbial community diversity at sites where anthropogenic land use is minimal and uniform across sampling localities.…”
mentioning
confidence: 99%
“…Microorganisms are able to thrive under a variety of extreme conditions including strongly acidified soils and metal-rich mineralized zones [1][2][3]. Some metal-tolerant bacteria in these environments are able to carve out niche existences by using the available metal and metal-containing compounds as sources of nutrition and energy [4].…”
Section: Introductionmentioning
confidence: 99%